Microbial succession and its correlation with the dynamics of volatile compounds involved in fermented minced peppers - Ma, Ding; Li, Yong; Chen, Chengcheng; Fan, Shichao; Zhou, Yi; Deng, Fangming; Zhao, Lingyan (Frontiers in Nutrition, 2022)
Fermented minced peppers are a traditional fermented food that has a unique flavor due to various microbial communities involved in fermentation. Understanding the changes in microbial communities and volatile components of fermented minced peppers is particularly important to unveil the formation of unique flavor of fermented peppers. In this study, the microbial communities and volatile compounds in fermented minced pepper was analyzed by high-throughput sequencing and GC-MS, as well as their underlying correlations were also established. Results indicated that 17 genera were identified as dominant microorganisms in the fermentation of minced pepper, accompanied by the detection of 64 volatile compounds. Further hierarchical clustering analysis (HCA) displayed that dynamic change of volatile metabolites were involved in the fermentation process, where alkane volatile components were mainly generated in the early stage (3–5 days), and alcohols volatile components were in the middle stage (7–17 days), while ester volatile components were mainly produced in both the early stage (3–5 days) and last stage (17–20 days). Bidirectional orthogonal partial least squares (O2PLS) analysis revealed that 11 genera were core functional microorganisms of fermented minced pepper. Cladosporium and Hansenpora were significantly correlated with the formation of 9 and 6 volatiles, respectively. These findings provide new insights into aroma profile variation of fermented minced peppers and underlying mechanism of characteristic aroma formation during fermentation.